Tratamento da papilomatose canina com Propionibacterium acnes - Megid, Jane [UNESP] (2001)
Propionibacterium acnes as immunostimulant in oral canine papillomatosis treatment in 16 animals was studied. Regression of the pappiloma started being observed after the second aplication, with complete resolution in all dogs after the sixth aplication. These results suggest the use of P. acnes as an alternative in oral canine papillomatosis therapy.